Adverse Outcomes of IVF/ICSI Pregnancies Vary Depending on Aetiology of Infertility - Kuivasaari-Pirinen, Paula (International Scholarly Research Network, 2012)
In vitro fertilization (IVF) is a risk factor for pregnancy, but there have been few studies on the effect of infertility's aetiology. Thus, we have assessed the role of aetiology on IVF pregnancy outcomes in a retrospective cohort study comparing the outcomes of IVF singleton pregnancies with those of spontaneous pregnancies in the general Finnish population. The study group consisted of 255 women with births resulting from singleton IVF pregnancies. Six subgroups were formed according to the following causes of infertility: anovulation (27%), endometriosis (19%), male factor (17%), tubal factor (15%), polycystic ovary syndrome (11%), and unexplained infertility (12%). The reference group consisted of 26,870 naturally conceived women. Adjusted odds ratios (AORs), for confounding factors such as age and parity, were estimated using logistic regression analysis. Women with endometriosis and anovulation had increased risks of preterm birth (AOR 3.25, 95% CI 1.5–7.1 and AOR 2.1, and 95% CI 1.0–4.2, resp.), while women in couples with male factor infertility had a twofold risk of admission to neonatal intensive care (AOR 2.5, 95% CI 1.2–5.3). The findings show that the aetiology of infertility influenced the obstetrics outcome, and that pooling results may obscure some increased risks among subgroups.